Sleep Patterns, Genetic Susceptibility, and Incident Chronic Kidney Disease: A Prospective Study of 370 671 Participants - Zhang, Haojie; Wang, Bin; Chen, Chi; Sun, Ying; Chen, Jie; Tan, Xiao; Xia, Fangzhen; Zhang, Jihui; Lu, Yingli; Wang, Ningjian (Frontiers in Neuroscience, 2022)
Abstract Objectives: Unhealthy sleep behaviors may be potential risk factors for chronic kidney disease (CKD). We aimed to examine the associations of combined sleep patterns and genetic susceptibility with incident CKD. Methods: This large-scale prospective cohort study included 370,671 participants without CKD at baseline in UK Biobank data. Five sleep behaviors were made up of sleep duration, insomnia, snoring, chronotype, and daytime sleepiness according to questionnaire. Overall sleep patterns by summing the five scores were created. Weighted genetic risk score of kidney function was calculated. Incident CKD was recorded from death register, primary care, and hospital inpatient records. Results: During a median follow-up of 10.6 years (about 3.9 million person-years), we documented 6365 patients with incident CKD. In five sleep behaviors, sleep 7-8h/day, free of insomnia and no frequent daytime sleepiness were independently associated with incident CKD, with a 12% (95%CI 7-16), 9% (3-14), 13% (9-18) lower risk, respectively. Compared to those with a sleep score of 0-1, participants with a score of 5 had a 21% (10-31%) lower risk of CKD. 17.1% of CKD in this cohort could be attributed to total poor sleep pattern. Participants with high genetic risk and intermediate or poor sleep pattern showed the highest risk of CKD (RR 2.58, 2.24-2.96; RR 2.59, 2.02-3.32, respectively), although there was no significant interaction between sleep patterns and genetic risk categories. In subgroup analysis, a significant interaction was found between sleep score and age group (<60yrs RR 0.87, 0.83-0.91; ≥60yrs RR 0.95, 0.92-0.97; P interaction <0.001). Conclusion: In this large prospective study, participants with a healthy sleep pattern was associated with a significant reduction of incident CKD risk no matter they had a high, intermediate, or low genetic risk.